1977
DOI: 10.1128/aac.11.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Penicillin on Streptomycin Production by Streptomyces griseus

Abstract: The correlation between the biosynthesis of the cell wall and the formation of streptomycin (SM) in Streptomyces griseus, influenced by a specific inhibitor of cell wall synthesis, was investigated. Penicillin, in subinhibitory concentrations (1 to 5 ,ug/ml), was added to cultures of S. griseus in different stages of its life cycle. The inhibitor decreased SM production, when young cultures were treated; however, there was an increase in SM formation when penicillin was added to older cultures. The explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Penicillin, a well-known inhibitor of cell wall synthesis, at a subinhibitory concentration (1-5 Ilg/ml) increased streptomycin production about twofold when added to older cultures (BARABAS and SZABO 1977). However, when added to younger cultures it decreased production, so that penicillin seems not to control the utilization of D-glucosamine in young cells, but influences the permeability of the mature cell wall.…”
Section: Correlation With Cell Wall Biosynthesismentioning
confidence: 97%
“…Penicillin, a well-known inhibitor of cell wall synthesis, at a subinhibitory concentration (1-5 Ilg/ml) increased streptomycin production about twofold when added to older cultures (BARABAS and SZABO 1977). However, when added to younger cultures it decreased production, so that penicillin seems not to control the utilization of D-glucosamine in young cells, but influences the permeability of the mature cell wall.…”
Section: Correlation With Cell Wall Biosynthesismentioning
confidence: 97%
“…Searching for the biological role of the aminoglycoside antibiotics, we found that streptomycin and neomycin were present in the cell wall of Streptomyces griseus and Streptomyces fradiae, respectively (2,3,14). We introduced a model to study the release of streptomycin from the spores of S. griseus strains to try to answer the question.…”
mentioning
confidence: 99%
“…When we started to study the biological role of streptomycin, an aminoglycoside-type antibiotic, we found a correlation between cell wall synthesis and antibiotic synthesis (1-3; G. Barabas, Folia Microbiol. 18:266, 1973); various inhibitors of cell wall synthesis increased the production of streptomycin (2).Since both the cell wall and streptomycin contain significant amounts of carbohydrate, we supposed that a common precursor exists for the two biosynthetic pathways. The search for this common precursor resulted in the isolation of a molecule of unknown structure (compound X) possessing antibiotic activity.…”
mentioning
confidence: 99%
“…Some of this speculation has been supported by experimental results (1,12,13); other speculations were, however, purely hypothetical in nature. When we started to study the biological role of streptomycin, an aminoglycoside-type antibiotic, we found a correlation between cell wall synthesis and antibiotic synthesis (1-3; G. Barabas, Folia Microbiol. 18:266, 1973); various inhibitors of cell wall synthesis increased the production of streptomycin (2).…”
mentioning
confidence: 99%